Respuesta :

Answer:

f  ( x )  − 1  = ( 1/ 4  x )  − 2.

Step-by-step explanation:        

For inverse function, the x and y interchanges and then make y the subject again of the equation. See the working out below:

f  ( x )  =  4 x  +  8

 f  ( x )  =  y

y    =  4 x  +  8

 x  =  4 y  + 8  ----- interchanging  y  and  x

Now make  y  the subject of the equation:

x  =  4 y  +  8

 − 4 y  =  -   x  +  8

 y  =  ( − 1/ 4  ) .  −  x   +  ( − 1/ 4  )  .8

 y  =  ( 1/ 4  x )  − 2

So the inverse function is:

f (x)  − 1  =  ( 1/ 4  x )  − 2

ACCESS MORE